Polissacarídeos de Alga Marinha Gracilaria birdiae (Plastino e Oliveira): Estrutura e Avaliação Toxicológica - Chaves, Luciano de Sousa (2008)
Seaweeds beings are classified in the Kingdom Protist, predominantly aquatic and with great adaptive capacity. Found in all regions of the planet, algae play an important role ecological and economic, representing a great potential for biorrecursos. The red seaweed Gracilaria birdiae, submitted to aqueous extraction of polysaccharides, showedyield of 6.4% in the cold extraction (25-28 ºC) (Gb-f), and 56 % in the hot extraction, at 100 °C (Gb-f). The sulfate content of the fractions Gb-f and Gb-q showed values of 6.4 and 3.6 %, respectively. The sulfate degree of Gb-f was 0.22, whereas Gb - q showed value of 0.04. The protein content in the samples Gb - f e Gb - q was 7.6 and 2.0%, respectively. The samples were characterized by Gel Permeation Chromatography (GPC), Infrared (FT-IR) and Nuclear Magnetic Resonance (NMR) spectroscopy. The GPC chromatograms of both samples showed similarity and typical characteristics of red seaweeds polysaccharides. The fraction Gb-f showed a peakand a shoulder with molecular weight of 1.11 x 106 and 1.26 x 105 g/mol, respectively, whereas, the fraction Gb - q showed both a peak and a shoulder, with molecular weight of 3.18 x 105 and 1.09 x 105 g/mol, respectively. The infrared spectra of Gb-f and Gb-q presented s imilar profiles, with bands characteristics of agarocolloids, more specifically agaran - like, with evidence of protein. NMR 1 D and 2 D were employed to the structural characterization of the samples Gb - f and Gb - q and revealed that they were composed by (1 →3) - β - D - galactopyranosyl linkage to (1→4) - α - L - anhydrogalactopyranosyl segments. The acute toxicological evaluation in mice demonstrated the absence of signs of toxicity with no mortality in the groups submited to polysaccharides treatment, by intraperitone al way, at doses of 0.5; 1.0 e 2.5 mg/100g of body weight. The sub chronic toxicological analysis evidenced no toxicity signs in rats, in the 50 mg/g body weight dosage, by oral way. The parameters evaluated were: animal body followed during 90 days of exp eriment, hematological and chemical analysis (counting of leukocities, glucose, total protein, creatinnin, cholesterol, AST and ALT dosages) and hystopatological analyses (spleen, liver, kidney, lung, hearth, stomach and gut).